2021
DOI: 10.1002/ptr.7101
|View full text |Cite
|
Sign up to set email alerts
|

Administration of isoliquiritigenin prevents nonalcoholic fatty liver disease through a novel IQGAP2‐CREB‐SIRT1 axis

Abstract: Isoliquiritigenin (ISO) is a flavonoid extracted from the root of licorice, which serves various biological and pharmacological functions including antiinflammatory, antioxidation, liver protection, and heart protection. However, the mechanism of its action remains elusive and the direct target proteins of ISO have not been identified so far. Through cell-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 69 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Altered expression of CEACAM1 [176], ACSL1 [285], STAT1 [286], TLR4 [287], ABCA1 [288], TLR5 [183], F2RL1 [289], CYP2D6 [290], PDK4 [291], RNF213 [186], JAK2 [292], TLR8 [189], NOTCH2 [293], CENPJ (centromere protein J) [294], FNIP1 [295], TLR2 [296], KIDINS220 [297], DUSP6 [298], CYP1B1 [299], S1PR3 [300], NCOA2 [301], HDAC9 [302], PELI1 [303], EGR1 [304], HIF1A [305], CCR2 [306], IRAK3 [307], KLF3 [308], VEGFA (vascular endothelial growth factor A) [309], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [310], PHLPP1 [213], FMR1 [311], IGF2R [312], PRKAR1A [313], WDR11 [314], LDLR (low density lipoprotein receptor) [315], TLR6 [316], SIRT1 [317], ALDH1A1 [318], NOD2 [319], ACSL4 [320], ELOVL6 [321], VCAN (versican) [322], CLIC5 [323], CLCN3 [324], OSBPL11 [162], HELZ2 [325], TET2 [326], KDM6A [327], PHF2 [328], PHGDH (phosphoglycerate dehydrogenase) [329], VEGFB (vascular endothelial growth factor B) [330], ZBTB7A [331], PC (pyruvate carboxylase) [332], CCR7 [333], PRDX2 [334], MAF1 [335], HSPB1 [336], ESF1 [281], LGALS3 [337], OLFM2 [338] and HDAC11 [339] had been confirmed in obesity. CEACAM1 [340], ACSL1 [341], TLR4 [342], ABCA1 [343], TLR5 [344], CYP2D6 [345], JAK2 [346], NOTCH2 [347], DDX3X [348], NCOA4 [349], EGR1 [350], IQGAP2 [351], GCLC (glut...…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of CEACAM1 [176], ACSL1 [285], STAT1 [286], TLR4 [287], ABCA1 [288], TLR5 [183], F2RL1 [289], CYP2D6 [290], PDK4 [291], RNF213 [186], JAK2 [292], TLR8 [189], NOTCH2 [293], CENPJ (centromere protein J) [294], FNIP1 [295], TLR2 [296], KIDINS220 [297], DUSP6 [298], CYP1B1 [299], S1PR3 [300], NCOA2 [301], HDAC9 [302], PELI1 [303], EGR1 [304], HIF1A [305], CCR2 [306], IRAK3 [307], KLF3 [308], VEGFA (vascular endothelial growth factor A) [309], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [310], PHLPP1 [213], FMR1 [311], IGF2R [312], PRKAR1A [313], WDR11 [314], LDLR (low density lipoprotein receptor) [315], TLR6 [316], SIRT1 [317], ALDH1A1 [318], NOD2 [319], ACSL4 [320], ELOVL6 [321], VCAN (versican) [322], CLIC5 [323], CLCN3 [324], OSBPL11 [162], HELZ2 [325], TET2 [326], KDM6A [327], PHF2 [328], PHGDH (phosphoglycerate dehydrogenase) [329], VEGFB (vascular endothelial growth factor B) [330], ZBTB7A [331], PC (pyruvate carboxylase) [332], CCR7 [333], PRDX2 [334], MAF1 [335], HSPB1 [336], ESF1 [281], LGALS3 [337], OLFM2 [338] and HDAC11 [339] had been confirmed in obesity. CEACAM1 [340], ACSL1 [341], TLR4 [342], ABCA1 [343], TLR5 [344], CYP2D6 [345], JAK2 [346], NOTCH2 [347], DDX3X [348], NCOA4 [349], EGR1 [350], IQGAP2 [351], GCLC (glut...…”
Section: Discussionmentioning
confidence: 99%
“…Limited proteolysis combined with mass spectrometry (LiP‐SMap) was done according to a former report 23,24 . Briefly, adipocyte lysates from three independent biological replicates were aliquoted in equivalent volumes containing 100 μg of proteome sample and incubated for 10 min at 25°C with vehicle or TA (final concentration: 33 nmol).…”
Section: Methodsmentioning
confidence: 99%
“…Limited proteolysis combined with mass spectrometry (LiP-SMap) was done according to a former report. 23,24 Briefly, adipocyte lysates from three independent biological replicates were aliquoted in equivalent volumes containing 100 μg of proteome sample and incubated for 10 min at 25°C with vehicle or TA (final concentration: 33 nmol). Proteinase K from Tritirachium album (Sigma Aldrich) was added simultaneously to all the proteome-TA samples at a proteinase K to substrate mass ratio of 1:100 and incubated at 25°C for 5 min.…”
Section: Limited Proteolysis Combined With Mass Spectrometrymentioning
confidence: 99%
“…Hence, SIRT1 activity is required to activate the transcription of PPARα target genes including FGF21 in the liver [ 86 ]. Moreover, it has been reported that natural compounds and drugs used for the treatment of NAFLD targeting the PPARα signaling pathway are dependent on SIRT1 activity [ 87 , 88 , 89 ]. Moreover, in both adipocytes and hepatocytes, it has been shown that the depletion of SIRT1 reduces the expression of several PPARα target genes related to lipid metabolism and mitochondrial biogenesis [ 90 , 91 ].…”
Section: Epigenetic Interaction Partners In Crime In Pparα-dependent ...mentioning
confidence: 99%